Challenges in Electronic Government Procurement (e-GP): a case study on e-GP in Directorate of Secondary and Higher Education (DSHE) - Mamun, S.M.A.A. (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2018.